Does Anticholinergic Burden Influence Therapeutic Success in Patients with Treatment-naïve Overactive Bladder? - João Oliveira; Simão Oliveira; Luís Vale; Cyrille Guillot-Tantay; Fabiana Cancrini; Mikolaj Przydacz; Paolo Geretto; Sabrina de Cillis; Véronique Phé; Nadir I. Osman; João Silva; Tiago Antunes-Lopes (European Urology Open Science)
Background and objective: Overactive bladder (OAB) is a bothersome condition for which anticholinergic drugs remain a cornerstone treatment. However, many patients have comorbidities that require treatment with medications that have anticholinergic properties, which contribute to what is known as the anticholinergic burden (ACB). Our aims were (1) to describe ACB in a treatment-naïve OAB cohort, (2) to analyze prescription trends according to ABC status, and (3) to study the impact of ACB on OAB treatment success. Methods: We reviewed all patients referred to our outpatient clinic for OAB in 2021 and 2022. Exclusion criteria were applied to select only patients with treatment-naïve idiopathic OAB. ACB status was assigned using the Drug Burden Index (DBI). Key findings and limitations: We included 102 treatment-naïve patients with OAB. OAB wet was the most frequent presentation. An anticholinergic drug was the initial treatment in 98% of cases. The median DBI was 0.09 (range 0–3.07). Anticholinergic drugs were the therapy most frequently prescribed across all DBI groups (DBI 0 vs 0–1 vs >1). At follow-up, 61.5% of patients reported an improvement with their prescribed therapy. Stratified by DBI status, the proportion of patients reporting an improvement after anticholinergic therapy was 77.1% in the DBI 0 group, 52% in the DBI 0–1 group, and only 25.9% in the DBI >1 group. DBI was significantly higher in the subgroup of patients reporting no improvement than in the subgroup who reported an improvement. This result was confirmed in a binary logistic regression model. Conclusions and clinical implications: Anticholinergic agents were the drugs most frequently prescribed for OAB, irrespective of DBI. Higher ACB was associated with worse treatment outcomes, which confirms that ACB is an important determinant of the success of anticholinergic therapy for OAB. Patient summary: We looked at how some drugs can affect treatment for overactive bladder (OAB), which is a condition involving sudden urges to urinate. Patients taking high quantities of these drugs before treatment for their OAB may not see as much of a benefit from additional similar drugs. This highlights the importance of tailoring treatments for individual patients according to the medications they are already taking.